Moral Education Values ​​in Sang Kiai Film (Teun Van Dijk Discourse Analysis): Nilai-nilai Pendidikan Akhlak Dalam Film Sang Kiai ( Analisis Wacana Teun Van Dijk) - Nur, Firda Ardianti; Romadlon, Dzulfikar Akbar (Indonesian Journal of Education Methods Development, 2022)
This study aims to find out what the values ​​of moral education are contained in the Sang Kiai film and how the social cognition is behind the scenario writer in making the Sang Kiai film script. The type of research used is descriptive qualitative research with data analysis techniques using discourse analysis of Teun Van Dijk. Based on the results of research that has been analyzed using three elements, namely the macro structure, super structure and micro structure, it is found that several values ​​of moral education are shown or shown in the Sang Kiai film including: sincere behavior, humbleness or humility, responsibility, compassion, fear of Allah SWT. , be devoted both to parents, and stay away from prejudice to others, regarding the social cognition contained in the film Sang Kiai is about the struggle of KH Hasyim Asyari who did not want to compromise with the invaders and the obstacles that KH Hasyim Asyari had to go through. Which in this film is framed with the values ​​of moral education. The value of moral education shown in the film Sang Kiai can be implemented in everyday life both in the family, community, school and other places, so that it is expected to become a good habit.